(untitled) (REMUNOM, 2023)
The Control of Conventionality is a mechanism in which the compatibility of internal rules of a State in relation to international treaties is verified, so that devices that give precedence to the dignity of the human person are applied to the concrete case, by which the states have as a parameter not only the Constitution of his country, but also international treaties. The objective of the present research was to verify if there is incompatibility between the Rome Statute and the Federal Constitution of 1988. Bibliographical references obtained through doctrines, jurisprudence and legal provisions were used as means of research. Given this, it can be said that there is no conflict between the Rome Statute and the Brazilian Constitution.